Pembentukan Karakter Islami Remaja melalui Kegiatan Jam’iyah Diba’iyah di Desa Pagerwangi Balapulang Tegal - Umi Mahmudah; Alfa Latifatul Wahidah; Umum Budi Karyanto; Alfiyana Izzatir; Rofi'ah Rofi'ah; Diyah Nurul Fitriyati (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
The purpose of this study was to describe efforts to form Islamic character of youth with jam'iyah diba'iyah activities in Pagerwangi Village which included variables (1) teenage character, variable (2) jam'iyah diba'iyah. This research applies the mix methods method. The subjects in this study include members, alumni, Jam'iyah diba'iyah supervisors. The quantitative data instrument in this study used a questionnaire, while the qualitative data collection used observation data along with interviews. The sample in this research is 20 respondents. The data obtained were analyzed using a percentage descriptive method. The results of the questionnaire data research stated that the percentage of the implementation of jam'iyah diba'iyah activities was 81.25%, while the percentage of youth members of jam'iyah diba'iyah was 79.625%. And it is known that the success rate of forming Islamic character through jam'iyah diba'iyah activities shows a percentage of 80.4375% which means very good. As for efforts to form an Islamic character in jam'iyah diba'iyah activities in Pagerwangi village, namely through habituation both in organizing, socializing, and behaving, setting an example according to the characteristics of the Prophet, giving mauidzah hasanah and giving educational warnings and punishments